The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1093/bioinformatics/btg207
|View full text |Cite
|
Sign up to set email alerts
|

MedScan, a natural language processing engine for MEDLINE abstracts

Abstract: We present a general biomedical domain-oriented NLP engine called MedScan that efficiently processes sentences from MEDLINE abstracts and produces a set of regularized logical structures representing the meaning of each sentence. The engine utilizes a specially developed context-free grammar and lexicon. Preliminary evaluation of the system's performance, accuracy, and coverage exhibited encouraging results. Further approaches for increasing the coverage and reducing parsing ambiguity of the engine, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(141 citation statements)
references
References 9 publications
2
134
0
4
Order By: Relevance
“…For this specific purpose we use the information contained in the ResNet mammalian database from Ariadne Genomics (http://www.ariadnegenomics.com/) (Novichkova et al, 2003;Daraselia et al, 2004). We selected only the interactions included in the category of Promoter Binding and Direct Regulation.…”
Section: Gene Regulatory Network Reconstructionmentioning
confidence: 99%
“…For this specific purpose we use the information contained in the ResNet mammalian database from Ariadne Genomics (http://www.ariadnegenomics.com/) (Novichkova et al, 2003;Daraselia et al, 2004). We selected only the interactions included in the category of Promoter Binding and Direct Regulation.…”
Section: Gene Regulatory Network Reconstructionmentioning
confidence: 99%
“…Interestingly, this information then supports secondary studies concerned with the consistency of the information [18], methods to imitate manual curation [19] and the propagation of facts in the literature [20]. Other automated approaches to the curation of pathway information include the MedScan system [21,22].…”
Section: Related Workmentioning
confidence: 75%
“…It was observed that a F-score of 50.4% was achieved when tested on a general corpus randomly extracted from MEDLINE, which is impossible to those systems based on predefined semantic grammar rules. For example, MedScan [13] can only successfully parse and generate semantic structures for about 34% sentences randomly picked from MEDLINE. The recall rate of MedScan was found to be 21% [13].…”
Section: Resultsmentioning
confidence: 99%
“…For example, MedScan [13] can only successfully parse and generate semantic structures for about 34% sentences randomly picked from MEDLINE. The recall rate of MedScan was found to be 21% [13]. This demonstrated the robustness of the HVS model.…”
Section: Resultsmentioning
confidence: 99%